Konseling Kelompok untuk Meningkatkan Kepercayaan Diri Remaja Korban Kekerasan dalam Rumah Tangga (KDRT) - Marlina, Aisah (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2017)
This study aims to determine the effect of group counseling on increasing self-confidence in adolescent victims of domestic violence (domestic violence). The subjects in this study amounted to 5 teenagers consisting of 2 men and 3 women and joined in the 1 experimental group